HYALOMMA TRUNCATUM IN AN ASIAN ELEPHANT (ELEPHAS MAXIMUS) – A REPORT - E. Tamileniyan; A. Latchumikanthan; M. Veeraselvam; M. Sivachandran; R. Velusamy (Indian Journal of Veterinary and Animal Sciences Research, 2026)
Physical   examination   of   an   adult   female  Asian   elephant   (Elephas maximus) housed at the M.R. Palayam Elephant Rescue and Rehabilitation Centre, Tiruchirapalli Forest Division,revealed tick infestation in the axillary region Based on distinct morphological characters such as medium body size, long mouth parts, dark brown integument with banded legs, squarish adanal plates, posteriorly placed anal groove and large oval to comma-shaped spiracular plates, the ticks were identified as Hyalomma truncatum. The case marks the first report on its occurrence on Asian elephants from Tamil Nadu, India.